BIM adoption model for small and medium construction organisations in Australia. Issue 2 (16th August 2018) - Hong, Ying; Hammad, Ahmed W.A.; Sepasgozar, Samad; Akbarnezhad, Ali
Abstract : Purpose: The purpose of this paper is to present a model for building information modelling (BIM) implementation at small and medium-sized construction contractor organisations (SMOs). The proposed BIM adoption model assesses BIM implementation benefits, costs and challenges faced by SMOs. Correlation between BIM adoption in SMOs and the associated impacting factors, including knowledge support and BIM adoption motivation, is captured through the model. Design/methodology/approach: A literature review of BIM adoption in construction was first presented. Research data, collected from 80 SMOs in Australia through a conducted survey, are then analysed. Descriptive analysis and structural equation modelling were used to investigate SMOs' understanding of BIM, and to qualify the correlations among the proposed latent variables impacting BIM implementation at SMOs, respectively. Additionally, this study used χ 2 test to compare differences between BIM users and non-BIM users regarding BIM understanding, interested applications and attitudes towards implementation benefits and challenges. Findings: Potential benefits associated with BIM implementation are a major motivation factor when it comes to BIM adoption at SMOs. In addition, existing staff's capability in using BIM tools positively affects the establishment of an organisational knowledge-support system, which determines the decision of adopting BIM eventually. Ultimately, there is a need for further emphasis on staff engagement in the implementation process. Research limitations/implications: The results presented in this paper are applicable to SMOs in the building sector of construction. BIM implementation at organisations involved in non-building activities, including civil works and infrastructure, needs to be assessed in the future. Practical implications: The results indicate that rather than placing the focus mainly on benefits of BIM implementation, successful implementation of BIM in practice requires adequate effort to assess implementation problems, establish knowledge support and engage staff in using BIM. Originality/value: Results of this study provide an insight into the adoption challenges of BIM in SMOs, given that the focus of previous studies has been mostly placed on BIM adoption in architectural firms and large contractors.